Kababaihan [videorecording] a Filipina portraits - Boti, Marie; Guy, Malcolm (Quezon City Asia Visions, 1989)
A documentary on the militant women's movement in the Philippines.
Editor, Lynda Peers; original music, Louise Poirier; narration, Augusta Lapaix; interviews, Patricia Youzwa, Marie Boti.
Keywords: Women -- Philippines; Sociology